Antennas for global navigation satellite systems - Chen, Xiaodong, 1962-; Wiley InterScience (Online service) (Chichester, West Sussex, U.K. ; Hoboken, N.J. : John Wiley & Sons, 2012)
"In this book, the authors discuss the various aspects of GNSS antennas, including fundamentals of GNSS, design approaches for the GNSS terminal and satellite antennas, performance enhancement techniques and effects of user's presence and surrounding environment on these antennas. In addition, the book will provide the reader with an insight into the most important aspects of the GNSS antenna technology and lay the foundations for future advancements. It also includes a number of real case studies describing the ways in which antenna design can be adapted to conform to the design constraints of practical user devices, and also the management of potential adverse interactions between the antenna and its platform."--
Front Matter -- Fundamentals of GNSS -- Fundamental Considerations for GNSS Antennas -- Satellite GNSS Antennas -- Terminal GNSS Antennas -- Multimode and Advanced Terminal Antennas -- Terminal Antennas in Difficult Environments -- Human User Effects on GNSS Antennas -- Mobile Terminal GNSS Antennas -- Appendix A: Basic Principle of Decoding Information from a CDMA Signal -- Appendix B: Antenna Phase Characteristics and Evaluation of Phase Centre Stability -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Antennas (Electronics); Global Positioning System; Space vehicles -- Radio antennas; Radio wave propagation; Mobile communication systems; Antennas (Electronics); Global Positioning System; Space vehicles -- Radio antennas; Radio wave propagation; Mobile communication systems; TECHNOLOGY & ENGINEERING -- Telecommunications; Antennas (Electronics); Global Positioning System; Mobile communication systems; Radio wave propagation; Space vehicles -- Radio antennas; Antennas (Electronics); Global Positioning System; Space vehicles / Radio antennas; Radio wave propagation; Mobile communication systems; Electronic books